Innovating Biology Education through Google Sites–Integrated Problem-Based Learning to Enhance Students’ Critical Thinking Skills and Learning Outcomes - Muhammad Zulkarnain Ramadana Asir; Lambang Subagiyo; Sukartiningsih; Susilo; Akhmad; Krishna Purnawan Candra (Jurnal Penelitian Pendidikan IPA, 2026)
This study aims to develop Google Sites–based learning media integrated with the Problem-Based Learning (PBL) model on the topics of plant and animal tissues, with the goal of improving students’ critical thinking skills and biology learning outcomes. The research followed the ADDIE development model, encompassing five systematic stages: Analysis, Design, Development, Implementation, and Evaluation. The study involved 35 Grade XI science students at SMA Negeri 3 Samarinda, Indonesia. The research instruments comprised expert validation sheets, practicality questionnaires, critical thinking tests, and learning achievement assessments. Data were analyzed using a mixed-method approach, combining quantitative and qualitative techniques through descriptive statistics, paired-samples t-tests, and N-Gain analysis. The results indicated that the developed media achieved a very high level of feasibility according to expert validation, with average scores of 93.75% from media experts, 91.25% from subject matter experts, and 95.00% from language experts. Practical assessments received very positive responses from teachers (95.00%) and students (91.33%), demonstrating that the media was user-friendly, engaging, and functional. Furthermore, the media effectively improved students’ critical thinking skills and learning outcomes, with an overall N-Gain of 0.84 (high category) and critical thinking indicator gains ranging from 0.71 to 0.86. A key innovation was the integration of an interactive discussion feature using Canva within Google Sites, which promoted collaboration and meaningful learning. In conclusion, the Google Sites–based PBL media was highly feasible, practical, and effective for improving students’ critical thinking skills and learning outcomes in biology.